Risk of clinically significant depression in HIV‐infected patients: effect of antiretroviral drugs1. Issue 4 (11th November 2013) - Gutiérrez, F; García, L; Padilla, S; Álvarez, D; Moreno, S; Navarro, G; Gómez‐Sirvent, JL; Vidal, F; Asensi, V; Masiá, M; ,
<x xml:space="preserve">Abstract</x> Objectives We aimed to characterize depression in newly diagnosed HIV‐infected patients, to determine the effect of antiretroviral therapy (ART) on its incidence, and to investigate whether efavirenz use was associated with a higher risk, compared with non‐efavirenz‐containing regimens, in the Spanish CoRIS cohort. Methods CoRIS is a contemporary, multicentre cohort of HIV‐infected patients, antiretroviral‐naïve at entry, launched in 2004. Poisson regression models were used to investigate demographic, clinical and treatment‐related factors associated with a higher incidence of clinically significant depression to October 2010. Results In total, 5185 patients (13 089 person‐years) participated in the study, of whom 3379 (65.2%) started ART during follow‐up. The incidence rates of depression before and after starting ART were 11.68 [95% confidence interval (CI) 9.01–15.15] and 7.06 (95% CI 5.45–9.13) cases per 1000 person‐years, respectively. After adjustment, there was an inverse association between the occurrence of depression and the initiation of ART [incidence rate ratio (IRR) 0.53; 95% CI 0.28–0.99], while the likelihood of depression increased in patients of age > 50 years (IRR 1.94; 95% CI 1.21–3.12). Longer exposure to ART was associated with a decreased IRR of depression in unadjusted and adjusted analyses. The IRR for patients receiving < 2, 2–4 and > 4 years of ART was 0.72 (95% CI 0.36–1.44), 0.10 (95% CI 0.04–0.25) and 0.05 (95% CI 0.01–0.17), respectively, compared with ART‐naïve patients. This protective effect was also observed when durations of exposure to nonnucleoside reverse transcriptase inhibitor‐based regimens and efavirenz‐containing regimens were analysed separately. Conclusions The incidence of clinically significant depression was lower among HIV‐infected patients on ART. The protective effect of ART was also observed with efavirenz‐containing regimens.